TESTE DE NORMALIDADE PARA DADOS DE TEMPERATURA E UMIDADE DO AR - HART, MARCOS VICENTE; KUHN, MATEUS DIEL; SAWICKI, SANDRO; BATTISTI, GERSON (Salão do Conhecimento, 2025)
TESTE DE NORMALIDADE PARA DADOS DE TEMPERATURA E UMIDADE DO AR